Plan de mejora ante vulnerabilidades encontradas en implementaciones de sistemas gestores de bases de datos - Dávila Muñoz, Mayra Alexandra (2019)
The objective of this work was to elaborate an improvement plan in the face of the shortcomings found in two database management systems using two vulnerability detection tools, to contribute to the security of the information handled within the organizations. The development of this was done following the methodological process proposed by Magerit V3, which theoretically allowed to identify the threats, the level of risk exposure and the impact that would cause its materialization; determining the database management systems as the object of study. The qualitative and quantitative assessment of the threats and their respective analysis by means of tables was carried out, as well as the use of Nessus and Nexpose as vulnerability detection tools in order to know errors that may occur in practice and taking into account the solutions Suggested by these tools, of the realization of this theoretical and practical process, an improvement plan was obtained, which was developed in order to have a perspective of the process to be followed in order to correct the identified risks in time, contributing to the taking of the best decisions regarding the security of the database management systems that contain the information.